The Motives of Sudanese Tourists to Choose Bandung as A Tourism Destination - Musa, Hussein Gibreel; Qamari, Ika Nurul (Jurnal Manajemen Bisnis, 2020)
The motivation factor is one of the most important elements for choosing tourism destination, this study aims to find out the motives of Sudanese tourists for choosing Bandung as tourism destination, this research uses a Qualitative approach to describe this topic as phenomenological study, the study showed that the factor of culture, religion, behavior, nature, the experiences of former tourists, shopping, price, have a very big role in motive Sudanese tourists to choose Bandung as a tourist destination. This study shows that the factors of excellence tourist destinations in Bandung have important indicators including the type and nature of tourist attractions; service quality, physical and social environment, cost, accessibility, and behavior of local residents to tourists. Tourist destinations in Bandung in the view of some Sudanese tourists have high accessibility, leading tourist attractions in tourist destinations easily accessible because of good road conditions. In the regulation of traffic and transportation is very chaotic because the traffic rate of vehicles is so crowded. Decent accommodation and a complete and clear guide/instruction. The lowest score is the attribute of the accessibility of tourist destinations in Bandung.